2018
DOI: 10.1016/j.pcorm.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an acute care surgery model on general surgery service productivity

Abstract: BACKGROUND The Acute Care Surgery (ACS) model has been widely adopted by hospitals across the United States, with ACS services managing emergency general surgery (EGS) patients previously treated by general surgery (GS) services. We evaluated the operational and financial impact of an ACS service model on general surgeons at an academic medical center. METHODS Using WiseOR® (Palo Alto, CA), we compared surgical case volumes for the GS service two years before (October, 2013 - September, 2015) and two years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…19 While ACS service implementation has been shown to improve the lag time to operation, decrease LOS, and improve complication rates, the effects on hospital finances and cost effectiveness are less clear. 5,[20][21][22] For trauma centers and safety net institutions with heavily unfunded populations, maintenance of trauma services, elective services, and EGS services may be a strain on financial resources. 23 For our institution, this led to the creation of the hybrid TACS Service.…”
Section: Discussionmentioning
confidence: 99%
“…19 While ACS service implementation has been shown to improve the lag time to operation, decrease LOS, and improve complication rates, the effects on hospital finances and cost effectiveness are less clear. 5,[20][21][22] For trauma centers and safety net institutions with heavily unfunded populations, maintenance of trauma services, elective services, and EGS services may be a strain on financial resources. 23 For our institution, this led to the creation of the hybrid TACS Service.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated a multitude of benefits from the ACS model in terms of clinical outcomes, costs, and higher satisfaction of both ACS and GS surgeons. [2][3][4][5][6][7][8][9][10][11][12] In contrast to the traditional surgical service, the majority of operative cases on the ACS service are nonelective-a small proportion being immediately life threatening-with the large proportion being semielective, where the surgery should be performed early, usually within 24 hours, for optimal outcomes. Hence, for an effective ACS service, the ready availability of a staffed OR and 24/7 availability of a trained surgeon are paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, trauma surgeons have incorporated EGS in their scope of practice developing a new paradigm of care and the development of the new surgical discipline of ACS. Numerous studies have demonstrated a multitude of benefits from the ACS model in terms of clinical outcomes, costs, and higher satisfaction of both ACS and GS surgeons 2–12 . In contrast to the traditional surgical service, the majority of operative cases on the ACS service are nonelective—a small proportion being immediately life threatening—with the large proportion being semielective, where the surgery should be performed early , usually within 24 hours, for optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations